Globalization and the time-space reorganization - Bonanno, Alessandro; Cavalcanti, Josefa Salete Barbosa (Emerald, 2011)
This volume explores capital mobility under globalization by studying some of its salient consequences in agriculture and food in North and South America. It probes the manner in which capital mobility alters the organization of the temporal and spatial dimensions that characterize the reproduction of capital. This is an important aspect of globalization because it reproduces the tension between the constant attempt of agents of capitalism to expand their scope of action and accelerate the time of the reproduction of capital, and the fixed nature of the institutions and measures that are employed to regulate capitalism. The analysis of this contradictory aspect of globalization is presented in seven cases that, while global in scope and social implications, are located in North and South America. Areas examined include the organization of labor in the exportation of grapes, fruit producing regions of Argentina and Brazil, the changing character of small town Ontario, migration and farmers in Mexico, and North Atlantic salmon. These original pieces of empirical research are contextualized by the introduction and common themes underscored in the concluding chapter.
Keywords: Social Science -- Sociology -- Rural.; Social Science -- Agriculture & Food.; Social Science -- General.; Sociology.; Globalization.; elektronické knihy; electronic books